THE IMPACT OF ENVIRONMENTAL KNOWLEDGE AND SELF-TRANSCENDENCE TOWARD GREEN PURCHASE INTENTION ON STUDENTS - Nisrina Qotrunnada; Hery Toiba; Fitrotul Laili; Dwi Retno Andriani; Budi Setiawan (Socio-Economics/Agribusiness Department, 2023)
The increasing number of consumers’ purchase intention on green products can be seen through the rising number of individuals who are willing to pay more for these products, and it proves this problem has attracted the attention of many circles. This article aims to examine what factors can influence the growth of student purchase intention on green products. The expansion of the Theory of Planned Behaviour was carried out to include two factors that are expected to influence student purchase intention, namely environmental knowledge and self-transcendence. Cluster random sampling is used to select samples that previously have been calculated using the Taro Yamane formula and the Parel formula with a total sample size of 136 samples. The results processed with the SEM-PLS (Structural Equation Model - Partial Least Square) showed that environmental knowledge was found to be unable to influence student purchase intention on green products, this is supported by the statement that high knowledge is not always in line with attitudes and practices generated. Self-transcendence was found to affect the growth of student purchase intention in green products, and this can happen because self-transcendence can affect the formation of consumer purchase intention.